The Role Of Accounting Standards And Transparent Budget Management In Supporting The Public Sector: A Systematic Literature Review: - Yusuf, Muh. Silmi Kaffa; Haliah , Haliah; Nirwana, Nirwana (Journal of Management, Economic, and Accounting, 2025)
Effective public financial management is essential for the efficient allocation of public resources, enhanced accountability, and strengthened public trust. Within this framework, the implementation of International Public Sector Accounting Standards (IPSAS) and the promotion of budget transparency are two strategic components that contribute significantly to achieving good governance. This study systematically reviews the existing literature on the roles of accounting standards and budget transparency in supporting accountability and performance in the public sector. A Systematic Literature Review (SLR) methodology was employed, focusing on articles indexed in the Scopus database from 2015 to 2025. An initial pool of 125 articles was screened using defined inclusion criteria, resulting in 38 primary studies for in-depth analysis. The findings indicate that IPSAS adoption enhances the quality of financial reporting, fosters standard harmonization across countries, and builds stakeholder trust, particularly among international donors. Concurrently, budget transparency facilitates public participation, curbs corruption, and improves fiscal policy effectiveness and human development outcomes. Despite these benefits, several challenges persist, including limited human resource capacity, inadequate technological infrastructure, and socio-political resistance, especially in developing countries. Moreover, the relationship between budget transparency and governance quality is characterized by simultaneous causality. Therefore, public financial reform initiatives should integrate both elements in a synergistic and context-sensitive manner. This study provides valuable insights for policymakers, academics, and practitioners seeking to strengthen transparent, accountable, and welfare-oriented public financial management systems.